PERENCANAAN SISTEM INSTALASI ELEKTRIKAL PADA GEDUNG MAKO PASPAMRES JAKARTA METODE MATLAB - Achmad Ari; Yulizan Rizki (Jurnal Teknik Industri dan Elektro, 2026)
The electrical installation system planning in the MAKO PASPAMPRES building was carried out to meet the high power needs due to technological developments and the complexity of modern equipment. Considering the very vital function of the building, the electrical system must be designed to be reliable, efficient, and meet safety standards to avoid power supply disruptions. This study uses a MATLAB-based calculation method. Based on the calculation results, a total power of 442,116.8 Watts was obtained with a load current of 839.683 Amperes, a voltage of 380 Volts, and a power factor of 0.8. The total cable resistance value is 0.36439 ohms, which causes a voltage drop of 14.543 Volts or 3.83%, still below the maximum allowable limit of 5%. In addition, the power losses that occurred were 16,921.62 Watts or around 3.83% of the total power. These results indicate that the planned electrical installation system has met the efficiency and reliability criteria, so it is suitable for application in the MAKO PASPAMPRES building.